A five‐CpG DNA methylation score to predict metastatic‐lethal outcomes in men treated with radical prostatectomy for localized prostate cancer. Issue 14 (28th June 2018) - Zhao, Shanshan; Leonardson, Amy; Geybels, Milan S.; McDaniel, Andrew S.; Yu, Ming; Kolb, Suzanne; Zong, Hong; Carter, Kelly; Siddiqui, Javed; Cheng, Anqi; Wright, Jonathan L.; Pritchard, Colin C.; et al.
Abstract : Background: Prognostic biomarkers for localized prostate cancer (PCa) could improve personalized medicine. Our group previously identified a panel of differentially methylated CpGs in primary tumor tissue that predict disease aggressiveness, and here we further validate these biomarkers. Methods: Pyrosequencing was used to assess CpG methylation of eight biomarkers previously identified using the HumanMethylation450 array; CpGs with strongly correlated ( r  >0.70) results were considered technically validated. Logistic regression incorporating the validated CpGs and Gleason sum was used to define and lock a final model to stratify men with metastatic‐lethal versus non‐recurrent PCa in a training dataset. Coefficients from the final model were then used to construct a DNA methylation score, which was evaluated by logistic regression and Receiver Operating Characteristic (ROC) curve analyses in an independent testing dataset. Results: Five CpGs were technically validated and all were retained ( P  < 0.05) in the final model. The 5‐CpG and Gleason sum coefficients were used to calculate a methylation score, which was higher in men with metastatic‐lethal progression ( P  = 6.8 × 10 −6 ) in the testing dataset. For each unit increase in the score there was a four‐fold increase in risk of metastatic‐lethal events (odds ratio, OR = 4.0, 95%CI = 1.8–14.3). At 95% specificity, sensitivity was 74% for the score compared to 53% for Gleason sum alone. The score demonstrated better prediction performance (AUC = 0.91; pAUC = 0.037) compared to Gleason sum alone (AUC = 0.87; pAUC = 0.025). Conclusions: The DNA methylation score improved upon Gleason sum for predicting metastatic‐lethal progression and holds promise for risk stratification of men with aggressive tumors. This prognostic score warrants further evaluation as a tool for improving patient outcomes.